Status consumption among Malaysian consumers - Heaney, Joo-Gim; Goldsmith, Ronald E; Wan Jusoh, Wan Jamaliah (The Haworth Press, Inc., 2005)
Status consumption describes individual differences in how much consumers purchase to attain social status. We investigated the relationships of status consumption with the constructs of materialism and attention-to-social-comparison-information in order to replicate the relationship of status consumption with the former and to extend its relationship to the latter. Multi-item self-report scales measured each construct. A survey of 239 Malaysian students provided the data. As hypothesized, status consumption was positively associated with both constructs, supporting its nomological validity and suggesting that promotional appeals to status seeking consumers might be more effective if they emphasize social comparisons.